Pengaruh Pendapatan Margin Murabahah Terhadap Peningkatan Modal Bank Syari’ah Mandiri - Trizuan Trizuan; Sandi Andika (LPPM ISNJ Bengkalis, 2019)
Murabahah financing is one of the most common types of contracts applied in Islamic banking financing activities. This is because most of the credit and financing provided by the banking sector in Indonesia relies on the consumer sector. The purpose of this study was to determine the effect of murabahah margin income on the increase in capital of Bank Syari'ah Mandiri. The research method used is a simple linear regression quantitative analysis. From the results of the coefficient of determination shows that murabahah margin income to increase the capital of Bank Syari'ah Mandiri has no significant effect, only contributing 6.6% and the remaining 93.4% can be explained by other factors such as liabilities, wadi'ah demand deposits, wadi'ah savings, burdens and mudharabah savings.